Pengaruh Pemberian Virgin Coconut Oil (VCO) pada Konsentrasi yang Berbeda terhadap Kadar Glukosa Darah Ayam - Puspita, Danar Pratiwi Diah; Suprihatin, Teguh (BULETIN ANATOMI DAN FISIOLOGI dh SELLULA, 2009)
The objective of this research was to know the effect of Virgin Coconut Oil (VCO) on chicken glucose blood. The research was designed by Completely Randomized Design (P0 : 0 cc/kg, P1 : 1.5 cc/kg, P2 : 3 cc/kg, and P3 : 6 cc/kg VCO/food). Data resulted from this research was analized by ANOVA and Duncan test. Conclusion of this research can be drawn that chicken glucose blood was significantly different between treatmen group. It means that VCO was not recomended as food suplement to chick.